If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + 3n = m Reorder the terms: 3n + 2p = m Solving 3n + 2p = m Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2p' to each side of the equation. 3n + 2p + -2p = m + -2p Combine like terms: 2p + -2p = 0 3n + 0 = m + -2p 3n = m + -2p Divide each side by '3'. n = 0.3333333333m + -0.6666666667p Simplifying n = 0.3333333333m + -0.6666666667p
| x-(6/13)=4/13 | | X+4=3x-18 | | -3(2x-9)+2x=43 | | 7.50t=187.50 | | 18x+11=2(6x+2)+6x+7 | | 4.2+2.1x=6.3 | | 18÷2/3 | | 3n+2p=m | | 400/-9 | | 2x^2-9=3 | | 15/96 | | 12n^2+4n= | | 2x+10+4=-8 | | M^3y-27y= | | 8(4-2n)=-16n+16 | | 5(1+c)=6(2-c) | | 66/0.03= | | x=4.32 | | 4.05*0.2= | | 4(x-5)2x-1+3= | | -2(c+4)=-50 | | 4x+2=-2x-16 | | 7x-9-5x=x-7x | | 2/3x-7==11 | | 40.5*0.2= | | M^3-27y= | | 215/90 | | 3c-4=a | | 1(3g-2)=g | | -138=-6(6x-1) | | 12+9=7y | | 7w+8w= |